PENGARUH ASET LANCAR, LEVERAGE, TOTAL ASSET TURNOVER TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN ECERAN TAHUN 2011–2015 DI BURSA EFEK INDONESIA - KHOSTITI NUR KHOULIN (Jurnal Manajerial, 2018)
The purpose of this study is to determine the effect of current assets, leverage, total asset turnover on profitability in Retail Trade Sub-Sector Companies in 2011-2015 on the Indonesia Stock Exchange. This research is a quantitative study, a population of 11 issuers listed on the Indonesia Stock Exchange for 5 consecutive years and earn profits from 2011-2015. The sample criteria used panel data with a total of 55 observations. The analysis technique used was multiple linear regression analysis. The independent variable of current assets, leverage, total asset turnover, dependent variable profitability. The results showed that current assets affect profitability, leverage affects profitability, while total asset turnover has no effect on profitability.